Use of field‐portable ultrasonography reveals differences in developmental phenology and maternal egg provisioning in two sympatric viviparous snakes - Sparkman, Amanda M.; Chism, Kenneth R.; Bronikowski, Anne M.; Brummett, Lilly J.; Combrink, Lucia L.; Davis, Courtney L.; Holden, Kaitlyn G.; Kabey, Nicole M.; Miller, David A. W. (Ecology and evolution, 2018)
A thorough understanding of the life cycles underlying the demography of wild species is limited by the difficulty of observing hidden life‐history traits, such as embryonic development. Major aspects of embryonic development, such as the rate and timing of development, and maternal–fetal interactions can be critical features of early‐life fitness and may impact population trends via effects on individual survival. While information on development in wild snakes and lizards is particularly limited, the repeated evolution of viviparity and diversity of reproductive mode in this clade make it a valuable subject of study. We used field‐portable ultrasonography to investigate embryonic development in two sympatric garter snake species, Thamnophis sirtalis and Thamnophis elegans in the Sierra Nevada mountains of California. This approach allowed us to examine previously hidden reproductive traits including the timing and annual variation in development and differences in parental investment in young. Both species are viviparous, occupy similar ecological niches, and experience the same annual environmental conditions. We found that T. sirtalis embryos were more developmentally advanced than T. elegans embryos during June of three consecutive years. We also found that eggs increased in volume more substantially across developmental stages in T. elegans than in T. sirtalis, indicating differences in maternal provisioning of embryos via placental transfer of water. These findings shed light on interspecific differences in parental investment and timing of development within the same environmental context and demonstrate the value of field ultrasonography for pursuing questions relating to the evolution of reproductive modes, and the ecology of development. We test for evidence of differences in the dynamics surrounding embryonic development in wild populations of two sympatric species using field‐portable ultrasonography. We find that these species differ in both developmental phenology and maternal provisioning to eggs, in spite of strong similarities in diet and habitat use, indicating lineage‐specific differences in timing of development and parental investment.